Digestibility of fat sources by sows - S Christianson; G L Allee; D S Pollmann (Kansas Agricultural Experiment Station Research Reports, 1984)
Twelve crossbred sows averaging 337 lb were used to determine apparent nutrient digestibility of three fat sources. Fat sources evaluated were soybean oil, a 85% dry-fat product composed of animal and vegetable fat, and a 80% dry- fat product made with casein encapsulated choice white grease. The control diet was a 13.0% crude protein corn-soybean diet with 8% cornstarch. Fat sources were added to the control diet to supply 8% added fat. The 12 sows were used in a crossover design, with three sows per diet in each of two periods. Each period consisted of a 5-day adjustment and a 5-day collection. Sows were fed 4.4 lb per day. Digestibility of dry matter, energy, and ether extract were significantly (P<.05) higher for diets containing soybean oil and the casein encapsulated choice white grease than for the dry fat product composed of animal and vegetable fat. Rate of passage increased when sows were fed the dry-fat product composed of animal and vegetable fat. These results suggest that dry-fat sources vary in nutritional value.; Swine Day, Manhattan, KS, November 15, 1984
Keywords: Swine day; 1984; Kansas Agricultural Experiment Station contribution; no. 85-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 461; Swine; Digestibility; Sows